ОРНИТОКОМПЛЕКСЫ ТРОСТНИКОВЫХ ЗАРОСЛЕЙ: СТРУКТУРА, ДИНАМИКА, ПРОБЛЕМЫ ОХРАНЫ - В.А. Кошелев (Zenodo, 2017)
The studies were conducted in 1996-2016 yy. in various types of water reservoirs in the southern, regions of Ukraine. The features of the formation, structure and dynamics of bird communities of, reeds, birds consorted connections with reeds Phragmites australis (Cav.) Trin. ex Steud. Are studied. Reeds are dominant among the hard surface vegetation on all the freshwater ponds in the region. The reeds consortium is formed quickly. The center of edificatory species is cane, which is formed around 4-5 concenters levels allocated, depending on the extent of other species, from the central nucleus of the form and its associated range of environmental constraints: trophic, topical, fabric, phoretic, exogenous and endogenous. Consorted connections of cane with birds are of the highest intensity in the summer. In autumn, winter and early spring reeds without leaves are sparse and less attractive to birds. The most noticeable and significant are topical connections (in the breeding season – 42 species of birds, during the spring migration – 18, during the autumn migration – 28, in winter – 22 species). Trophic, fabric and foretic connections are less pronounced. The obligate consorts (level 1) include12 species of birds, the optional ones (2nd level) – 30 species. The third concenter involves specialized species of birds of prey ( Circus aeruginosus Linnaeus, 1758; Circus pygargus , Linnaeus, 1758; Circus cyaneus Linnaeus, 1766; Falco peregrinus Tunstall, 1771; Buteo lagopus Pontoppidan, 1763; Accipiter nisus Linnaeus, 1758; Falco subbuteo Linnaeus, 1758; Asio flammeus Pontoppidan, 1763) that prey on large and small birds, rodents, large insects. Dense reeds are readily used for shelter from predators and to form mass night-stays for many birds (50 species). In summer, the flooded reedbeds were registered to have 82 species of birds, whereas the dry ones had only 4 species. In winter, reeds were noted to house 22 species of birds (topical and fabric connections, to a lesser extent - trophic). Fully formed ...